Design of Experiments for Generalized Linear Models - Russell, Kenneth G.; Taylor and Francis (Boca Raton, FL : Chapman and Hall/CRC, 2018)
Generalized Linear Models (GLMs) allow many statistical analyses to be extended to important statistical distributions other than the Normal distribution. While numerous books exist on how to analyse data using a GLM, little information is available on how to collect the data that are to be analysed in this way. This is the first book focusing specifically on the design of experiments for GLMs. Much of the research literature on this topic is at a high mathematical level, and without any information on computation. This book explains the motivation behind various techniques, reduces the difficulty of the mathematics, or moves it to one side if it cannot be avoided, and gives examples of how to write and run computer programs using R. Features The generalisation of the linear model to GLMs Background mathematics, and the use of constrained optimisation in R Coverage of the theory behind the optimality of a design Individual chapters on designs for data that have Binomial or Poisson distributions Bayesian experimental design An online resource contains R programs used in the book This book is aimed at readers who have done elementary differentiation and understand minimal matrix algebra, and have familiarity with R. It equips professional statisticians to read the research literature. Nonstatisticians will be able to design their own experiments by following the examples and using the programs provided.
Generalized Linear Models Background Material The Theory Underlying Design The Binomial Distribution The Poisson Distribution Several Other Distributions Bayesian experimental design.
Includes bibliographical references and index.
Also available in print format.
Keywords: binomial distribution; linear mixed models; linear models; mixture experiments; Poisson distribution; R software; Linear models (Statistics); Experimental design; Electronic books